Tenofovir alafenamide for the treatment of chronic hepatitis B virus infection. Issue 7 (3rd July 2017) - Abdul Basit, Syed; Dawood, Altaf; Ryan, John; Gish, Robert
ABSTRACT: Introduction : In April 2017 tenofovir alafenamide (TAF) was added to the list of first-line therapies recommended for chronic hepatitis B (CHB). TAF has pharmacology similar to tenofovir disoproxil fumarate (TDF) with higher cell delivery to the hepatocytes but less systemic exposure. Areas covered : We review here studies leading to TAF's approval and comparing it to TDF. In two major clinical trials, TAF was non-inferior to TDF in achieving HBV DNA levels below 29 IU/ml. TAF-treated patients had significantly smaller decreases in bone mineral density (BMD) at the hip and spine in both HBeAg-positive and HBeAg-negative patients, and smaller mean increases in serum creatinine, although the difference was only statistically significant in HBeAg-positive patients. Patients treated with TDF for 96 weeks and then switched to TAF had improvements in renal and BMD measures only 24 weeks after switching. Expert commentary : With clear evidence from major studies showing that TAF is safe, tolerable, and non-inferior to TDF, its recommendation as a first-line therapy is appropriate. Longer term follow up will be required to determine if the differences in adverse bone and kidney effects seen with TAF in comparison to TDF will be clinically relevant.